K voprosu o roli malyh stran v processah perestrukturirovanija postsovetskogo prostranstva (na primere Pribaltiki) - Smirnov V. (Балтийский регион, 2014)
This author analyses the 2013 Lithuanian presidency of the EU in the context of the Ukrainian crisis and evaluates the contribution of Latvia and Estonia (the former Soviet republics set to preside over the EU in 2015 and 2018) to the shift in the power balance in the post-Soviet space. Through assessing the actions of small countries in promoting the Eastern Partnership programme with an emphasis on the anti-Russian agenda, the author concludes that they will inflict harm on the EU in a long-term perspective. These former Soviet republics no longer rely on mere diplomacy, but resort to a whole new problematic narrative, where Russia is described as an “aggressive and unpredictable neighbour” that poses the “threat from the East.” Being more mobile, small countries are able to concentrate power and resources in one or several key areas. This makes it possible for these countries to take advantage of international politics (even if the consequences of such steps are miscalculated) and “feed” on it through — so metimes consciously — creating “conflict nodes” in the relations between major players. This is especially true in the case of states that do not bear responsibility for global stability.